Improvement in the Mortality-to-Incidence Ratios for Gastric Cancer in Developed Countries With High Health Expenditures - Yang, Tzu-Wei; Wang, Chi-Chih; Hung, Wei-Cheng; Liu, Yu-Hsiang; Sung, Wen-Wei; Tsai, Ming-Chang (Frontiers in Public Health, 2021)
The mortality-to-incidence ratio (MIR) is widely used to evaluate the efficacy of cancer management outcomes for individual countries. However, the association among health care expenditure, human development index (HDI), and changes in MIR over time (δMIR) remains unknown. We aimed to elucidate the significance between these indicators and gastric cancer outcomes in different countries. Among the regions, Asia had the highest number of new gastric cancer cases, gastric cancer-related deaths, age-standardized ratio of incidence, and mortality. Chile had the highest age-standardized ratio (ASR) for gastric cancer incidence and the highest ASR for mortality. Moreover, MIR was highest in Africa (0.91) and lowest in North America (0.43). Of note, MIR was negatively associated with HDI, current health expenditure (CHE) per capita, and CHE/GDP % and δMIR was positively associated with CHE/GDP % in countries with very high HDI. However, δMIR showed no significant associations with these indicators in the countries analyzed. In conclusion, increased HDI, CHE per capita, and CHE/GDP are associated with improved gastric cancer outcomes. In addition, the δMIR could be an indicator that can be used to evaluate the improvement in cancer management outcomes over time.